Taghayyuru Al-Nuqud Fi Al-Mu'awadhat Wa Al-'Ibadat Wa Al-Gharamat Al-Maliyyah - Asmuni Mth (Millah: Journal of Religious Studies, 2004)
The change of value currency had been the serious attention by the classical fiqh experts. Therefore, there are many different opinions about that, not only between mazhab to another, but also in the circle of one mazhab. The best interesting, the ulama not only connectedthe change ofvalue currency with transaction ofsale andpurchase, lease, loan, salary and other bussiness transactions, but also with zakah, family responsible, and diyat in the criminal cases also the minimal limit (counting) of the thief good value made the man cut his hand. The difference happened in this context, actually showed how the fiqh experts searched the transaction consequences in crisis condition in order one to another not make lose each other and finally may create the justice that one of the spirit of Islamic economy.